Black African Families’ Perceptions of A Girl Child Raised By A Single Father: Exploratory Study - Rammutla, Calphurnia Mmathato (Innovation Journal of Social Sciences and Economic Review, 2025)
This study aims to explore how Black African families perceive single fathers raising girl children, addressing persistent cultural beliefs that question fathers’ capability to nurture and care for daughters independently. By examining these perceptions, the study seeks to dispel myths and raise awareness within diverse ethnic groups where cultural customs remain deeply valued. The systematic review employed the PRISMA methodology to ensure transparency in reporting the purpose, methodology, and findings. Relevant empirical, peer-reviewed articles were identified through three search strategies, utilizing electronic databases such as ResearchGate, Google Scholar, Taylor & Francis, and Scopus. Articles published up to 15 September 2024 were included in the review. The findings reveal that traditional beliefs continue to perpetuate the view that fathers, particularly single fathers, are unfit to raise daughters. However, the review also highlights the evolving roles of fathers and the need for societal and legislative changes to support fathers’ involvement in caregiving. It emphasizes that fathers, when given adequate support and recognition, can effectively contribute to their children’s well-being. In conclusion, the study underscores the importance of revising policies, such as Section 33(1) of the Children’s Act 38 of 2005, to address the roles and responsibilities of mothers and fathers separately. This revision would promote equitable parenting practices and challenge entrenched cultural biases. The study contributes to the body of knowledge by encouraging a paradigm shift in the perception of fatherhood within Black African families and advocating for policy changes that empower fathers in caregiving roles.